The quadruplex fluorescent quantitative PCR method for the simultaneous detection of respiratory diseases in quail: Pasteurella multocida, Avibacterium paragallinarum, Mycoplasma gallisepticum, and Mycoplasma synoviae - Wang, Haojie; Xue, Lihong; Wang, Longxi; Liu, Yixuan; Chen, Jianxing; Sun, Yue; An, Tongqing; Li, Changwen; Chen, Hongyan; Yu, Changqing; Xia, Changyou; Zhang, He (Frontiers in Microbiology, 2025)
BackgroundThe quail farming industry constitutes an important component of China’s agricultural sector. However, it is frequently threatened by various bacterial and mycoplasmal infections, particularly respiratory diseases caused by Pasteurella multocida, Avibacterium paragallinarum, Mycoplasma gallisepticum, and Mycoplasma synoviae. These pathogens commonly result in co-infections or secondary infections, and their clinical presentations are often indistinguishable due to the similarity of symptoms.MethodsFour sets of primers and probes were designed based on the GenBank-registered gene sequences: the kmt1 gene of P. multocida, the recN gene of A. paragallinarum, the mgc2 gene of M. gallisepticum, and the vlhA gene of M. synoviae. Reaction conditions were optimized accordingly. A recombinant plasmid standard was constructed for the generation of standard curves. The sensitivity, specificity, reproducibility, and accuracy of the assay were systematically evaluated.ResultsThe constructed standard curves demonstrated strong linearity (R2 = 1.000, 0.998, 1.000, and 1.000), with high amplification efficiencies (107.09, 91.23, 112.10, and 125.51%, respectively). The detection limit for each recombinant plasmid standard was as low as 10 copies. No cross-reactivity was observed with non-target pathogens, including avian pox virus, Escherichia coli, Salmonella spp., Newcastle disease virus, infectious bronchitis virus, infectious laryngotracheitis virus, and Staphylococcus aureus. The assay exhibited excellent reproducibility, with inter- and intra-assay coefficient of variation (CV) values ranging from 0.11 to 1.41%. Among 126 clinical samples, P. multocida was detected in 6 samples, A. paragallinarum in 3, M. gallisepticum in 6, and M. synoviae in 4. These results were consistent with those obtained using previously established methods.DiscussionA highly sensitive, specific, rapid, and efficient quadruplex fluorescence quantitative PCR assay was successfully developed for the simultaneous detection and identification of Pasteurella multocida, Avibacterium paragallinarum, Mycoplasma gallisepticum, and Mycoplasma synoviae.